Routines, Generative Systems Analyzed as a Function Based on Time and Innovation - Júlio César da Costa Júnior; Marcos André Mendes Primo; Taciana de Barros Jerônimo (BBR: Brazilian Business Review)
This study aims to propose a model to study organizational routines as a generative system based on time and innovation. Routines are intrinsically related to resources orchestration processes, learning, know-how accumulation and organizational expertise. Over time, combined with innovations, in-process, or via technological artifacts, routines may contribute to diversifying the portfolio of outputs able to add value to a company result. The study follows a qualitative approach, with an applied nature, and was made through multiple case studies. Data collection was through semi-structured interviews and was beaconed by protocol subject to peers validation. The main contribution is the model which is proposed to understand routines as a generative system able to diversify the outputs or organizational actions enhancing the results arisen from innovations. Results have confirmed the relation between routines and resources orchestrations process, incorporation and development of innovations, and organizational learning.